Preparation method and application of formed molecular sieve catalyst

By using the molding method of synergistically acting two pore-generating agents in the olefin catalytic cracking catalyst, a catalyst with a porous structure is formed, which solves the problems of poor internal diffusion and insufficient reactivity, and significantly improves the reactivity and propylene selectivity.

CN119425770AActive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310959477.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14
Estimated Expiration
2043-08-01

AI Technical Summary

Technical Problem

In industrial applications, existing olefin catalytic cracking catalysts have problems such as poor internal diffusion, reactivity and insufficient propylene selectivity.

Method used

The pore structure and internal diffusion properties of the catalyst are optimized by the synergistic action of two pore-generating agents (first pore-generating agent and second pore-generating agent) to form a porous structure through molding and calcining.

Benefits of technology

The reaction activity and propylene selectivity are significantly improved, and the secondary side reaction caused by the retention of reaction products within the catalyst is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425770A_ABST
    Figure CN119425770A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a formed molecular sieve catalyst. The method provided by the invention comprises the following steps: S1, providing a first mixture comprising molecular sieve raw powder, a first pore-foaming agent and a second pore-foaming agent; s2, the first mixture in the S1 is subjected to forming treatment, and a formed product is obtained; and S3, roasting the molded product in the step S2 to obtain the molded molecular sieve catalyst. Wherein the length-diameter ratio of the first pore-foaming agent is greater than that of the second pore-foaming agent, the length-diameter ratio of the first pore-foaming agent is 50-10000, and the length-diameter ratio of the second pore-foaming agent is 0.5-50. The molded molecular sieve catalyst prepared by the method provided by the invention is used for olefin cracking propylene preparation tests, can effectively reduce secondary side reactions caused by retention of reaction products in the catalyst, and significantly improves the reaction activity and propylene selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to a preparation method of a shaped molecular sieve catalyst and application thereof. Background Art

[0002] Propylene is a basic chemical raw material, and its demand has been growing in recent years. However, the deterioration and shortage of crude oil raw materials have brought about increasingly prominent contradictions in propylene production. On the other hand, mixed C4 and above olefins and alkanes are by-products of ethylene plants, refinery FCC units and methanol to olefins units, and can usually only be used as low value-added products such as liquefied gas fuel. Therefore, it is of great significance to use olefin resources for further deep processing to produce high value-added products such as propylene and ethylene.

[0003] The active component of the catalyst for catalytic cracking of olefins is a hydrogen-type ZSM-5 molecular sieve. For example, in the previous process, CN1284109 disclosed a process for cracking olefins with carbon content of more than four to produce propylene and ethylene. The catalyst used was a hydrothermally modified ZSM-5 molecular sieve with a silicon-aluminum ratio greater than 200. In Example 3, the etherification carbon four cracking conversion rate was 54%, and the propylene yield was only 29%. There was only data for 160 hours of operation.

[0004] EPA0109059 discloses a method for cracking olefins with a carbon content of 4 or more to produce propylene and ethylene, using a ZSM-5 or ZSM-11 molecular sieve with a silicon-aluminum ratio of less than 360 as a catalyst, and the reaction must be carried out within 50 hours. -1 The reaction can only be carried out at a high space velocity to obtain a higher propylene yield, and the example shows that the reaction can only be maintained for dozens of hours, and the catalyst cokes and the reaction activity drops sharply.

[0005] US6307117 discloses a process in which a silver-containing ZSM-5 molecular sieve with almost no protonic acid is used to extend the catalyst regeneration cycle and avoid rapid catalyst coking. The process requires a high reaction space velocity (16 to 39 h -1 ), higher temperature (~600℃).

[0006] A common feature of these technologies is the use of molecular sieves as catalysts and a reaction space velocity as high as 10h -1 Therefore, the internal diffusion of the catalyst has a great influence on the reaction performance.

[0007] Molecular sieve catalysts, which are usually used for catalytic cracking of C4 olefins to produce propylene, need to be prepared into catalyst particles of a certain shape and suitable mechanical strength by adding a binder to the synthesized molecular sieve raw powder during industrial application. The use of binders, such as silica sol molding, will more or less block the pores on the surface of the molecular sieve grains, and the gaps between the molecular sieve grains inside the catalyst are very small. On the one hand, the reaction activity of the molecular sieve cannot be fully exerted. On the other hand, the reactants and products diffuse slowly inside the catalyst particles, which easily forms secondary reactions of the reaction products and affects the selectivity of the target products.

[0008] In order to improve the internal diffusion of the catalyst, a common method is to add a porogen with a certain particle size when the catalyst is formed, and use the space-occupying effect of the porogen to remove the porogen during calcination and other operations, leaving holes, thereby optimizing the pore structure of the catalyst or carrier. For example, invention patent CN 101623641A discloses a catalyst forming method with iron oxide powder as the main component, in which a microsphere particle porogen is added during catalyst forming to improve the catalyst porosity and reaction activity.

[0009] CN103041852A discloses that activated carbon fibers of appropriate length are introduced as porogens during the molding of TS-1 molecular sieve, thereby increasing the macropore volume ratio of the prepared catalyst.

[0010] In these existing technologies, the cavities formed by small particle porogens are mostly "cystic" shaped and enclosed inside the catalyst, and the pore openings are not smooth. Activated carbon fiber is expensive as a porogen, and the prepared pore structure is single. The olefin cracking catalysts prepared by the two methods have little effect on improving the diffusion effect inside the catalyst, and the reaction activity and propylene selectivity during olefin cracking are not significantly improved. Summary of the invention

[0011] In view of the problems existing in the prior art, the present invention provides a method for preparing a shaped molecular sieve catalyst and its application. The method provided by the present invention prepares a shaped molecular sieve catalyst for olefin cracking to propylene test, which can effectively reduce the secondary side reactions caused by the retention of reaction products inside the catalyst and significantly improve the reaction activity and propylene selectivity.

[0012] In a first aspect, the method for preparing a shaped molecular sieve catalyst of the present invention comprises the following steps:

[0013] S1: providing a first mixture including molecular sieve raw powder, a first porogen and a second porogen;

[0014] S2: subjecting the first mixture in S1 to a molding process to obtain a molded product;

[0015] S3: calcining the formed product in S2 to obtain the formed molecular sieve catalyst;

[0016] The aspect ratio of the first porogen is greater than that of the second porogen, the aspect ratio of the first porogen is 50-10000, and the aspect ratio of the second porogen is 0.5-50.

[0017] The first porogen and the second porogen used in the present invention are indispensable and have a synergistic effect. Specifically, during extrusion molding, the first porogen is axially arranged in the green body, and the second porogen is evenly distributed inside the catalyst. Through roasting, holes and narrow channels are formed, the holes connect the channels, and the channels connect the holes, so that the prepared catalyst has rich channel diameters, and the channel openings are transparent and well connected. In addition, the present invention can flexibly adjust the macropore diameter distribution of the catalyst by combining the first porogen and the second porogen with different aspect ratios, so that the prepared catalyst has more excellent internal diffusion performance, and promotes the heat transfer and mass transfer efficiency of the reaction process.

[0018] In some embodiments, the first porogen has an aspect ratio of 60, 80, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2300, 2500, 2700, 3000, 3300, 3500, 3700, 4000, 4300, 4500, 4700, 5000, 6000, 7000, 8000, 9000, or any value therebetween. In some embodiments, the aspect ratio of the first porogen is 100-2000. In some embodiments, the aspect ratio of the first porogen is 100-1000. When the aspect ratio of the first porogen is too high, the porogen fibers are too long. During the material mixing and kneading process, the porogens are entangled with each other and cannot be evenly dispersed, and cannot form evenly distributed pores in the catalyst. When the aspect ratio of the first porogen is too low, the fibers are too short, and most of the porogens are evenly dispersed and buried in the catalyst, forming "cyst" holes in the catalyst, and not forming enough openings on the catalyst surface, which is not conducive to the diffusion and separation of product molecules to cause secondary reactions, and the product selectivity is reduced.

[0019] In some embodiments, the aspect ratio of the first porogen is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 33, 35, 37, 40, 43, 45, 47 or any value therebetween. In some embodiments, the aspect ratio of the second porogen is 1-30. When the aspect ratio of the second porogen is too high, its effect is similar to that of the first porogen, and only straight channels can be formed, and the reaction conversion rate is slightly low. When the aspect ratio of the second porogen is too low, for example, the aspect ratio is significantly less than 1, the porogen particles are too small and too thin, and the gaps formed are very small, and the channels formed by the first porogen cannot be connected, and the selectivity effect on improving the reaction conversion rate is not obvious. Only when the porogen particle size is appropriate and the number is large, a large number of holes are formed in the catalyst, and a large number of areas that are easy to diffuse and contact are formed through the series connection of the first porogen, can the reaction activity of the catalyst and the selectivity of the product propylene be improved.

[0020] In the present invention, the aspect ratio of the fiber porogen is defined as its shape index, which is calculated as the ratio of length to diameter. The aspect ratio of spherical and powder particles is 1.

[0021] In some embodiments, the mass ratio of the second porogen to the first porogen is (0.05-20):1, for example, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1 or 19:1. In some embodiments, the mass ratio of the second porogen to the first porogen is (0.1-10):1.

[0022] In some embodiments, the first porogen is a long and thin fibrous porogen. In some embodiments, the second porogen is a short and thick fibrous or particulate porogen.

[0023] In some embodiments, the first porogen is selected from one or more of synthetic fibers and natural fibers. In some embodiments, the synthetic fibers are selected from one or more of nylon fibers, polyester fibers, nylon fibers, acrylic fibers, polyethylene fibers, polypropylene fibers, and polystyrene fibers. In some embodiments, the natural fibers are selected from one or more of broadleaf pulp fibers, coniferous pulp fibers, and straw fibers.

[0024] In some embodiments, the second porogen is selected from one or more of synthetic fibers, synthetic microspheres, microcrystalline cellulose, short fibers, activated carbon, starch, and graphite. In some embodiments, the synthetic fibers are selected from one or more of nylon fibers, polyester fibers, nylon fibers, acrylic fibers, polyethylene fibers, polypropylene fibers, and polystyrene fibers.

[0025] In some embodiments, the first mixture further includes a binder, an extrusion aid, and water.

[0026] In some embodiments, based on the mass of the molecular sieve raw powder and the dry-based binder, the mass content of the first porogen is 0.5%-20%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18% or 19%. In some embodiments, the mass content of the first porogen is 1%-10%.

[0027] In some embodiments, based on the mass of the molecular sieve raw powder and the dry-based binder, the mass content of the second porogen is 0.5%-20%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18% or 19%. In some embodiments, the mass content of the second porogen is 1%-10%.

[0028] In the present invention, the dry-based binder refers to the solid matter after the bound water is removed from the binder.

[0029] In some embodiments, based on the mass of the molecular sieve raw powder and the dry-based binder, the mass content of the binder is 5%-50%, for example, 7%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45%. In some embodiments, the mass content of the binder is 10%-30%.

[0030] In some embodiments, based on the mass of the molecular sieve raw powder and the dry-based binder, the mass content of the extrusion aid is 0.5%-15%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13% or 14%. In some embodiments, the mass content of the extrusion aid is 1%-8%.

[0031] In some embodiments, the extrusion aid is selected from one or more of sesbania powder, modified cellulose, glycerol and polycarboxylic acid.

[0032] In some embodiments, the binder is selected from one or more of silica sol, alumina sol, pseudo-boehmite and water glass.

[0033] In some embodiments, the molecular sieve is selected from one or more of the molecular sieves such as Y-type molecular sieve, ZSM-5 molecular sieve, ZSM-11 molecular sieve, ZSM-35 molecular sieve and mordenite. In some embodiments, the molecular sieve is selected from ZSM-5 molecular sieve.

[0034] In some embodiments, in S3, before calcining, the molded product is subjected to an aging treatment and a drying treatment in sequence.

[0035] In some embodiments, the temperature of the aging treatment is less than or equal to 80° C. In some embodiments, the temperature of the aging treatment is less than or equal to 50° C., such as 20° C., 30° C., or 40° C.

[0036] In some embodiments, the aging treatment time is 2h-48h, for example, 8h, 12h, 18h, 24h, 30h, 36h or 40h. In some embodiments, the aging treatment time is 5h-24h.

[0037] In some embodiments, the drying temperature is 100° C.-200° C., for example, 110° C., 130° C., 140° C., 160° C. or 180° C. In some embodiments, the drying temperature is 120° C.-150° C.

[0038] In some embodiments, the drying time is 5h-24h, for example 8h, 10h, 12h, 14h, 16h, 18h or 20h. In some embodiments, the drying time is 5h-15h.

[0039] In some embodiments, the calcination temperature is 200° C.-700° C., for example, 250° C., 300° C., 350° C., 400° C., 450° C., 500° C., 550° C., 600° C. or 650° C. In some embodiments, the calcination temperature is 450° C.-650° C.

[0040] In some embodiments, the calcination time is 1 h-10 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h or 9 h. In some embodiments, the calcination time is 2 h-8 h.

[0041] In some embodiments, the calcination temperature is achieved by programmed temperature increase, and the temperature increase rate is 20°C / h-50°C / h, for example, 25°C / h, 30°C / h, 35°C / h, 40°C / h or 45°C / h.

[0042] In some embodiments, the method for preparing the shaped molecular sieve catalyst comprises the following specific steps:

[0043] 1) The molecular sieve raw powder, the binder, the first porogen, the second porogen, the extrusion aid and water are fully kneaded in a kneader to form a uniform plastic body;

[0044] 2) subjecting the plastic body to a molding process, such as extrusion or pelletization, to prepare a catalyst body having a diameter in the range of 0.5-20 mm and a length of 0.5-20 mm;

[0045] 3) The green body is first aged in air at a temperature not exceeding 80°C for 2-48 hours, and then dried at 100-200°C for 5-24 hours; finally, the dried green body is calcined in an oxygen-containing atmosphere at a temperature of 300-700°C for 1-10 hours according to a programmed temperature increase to obtain a catalyst with a porous structure.

[0046] In a second aspect, the present invention provides the use of a shaped molecular sieve catalyst prepared by the preparation method described in the first aspect in a carbon four cracking reaction to produce olefins.

[0047] Beneficial technical effects of the present invention:

[0048] The method of the present invention adopts two porogens to prepare olefin cracking molecular sieve catalysts, which are used in olefin cracking to produce propylene experiments. Compared with the catalysts of the comparative examples, the secondary side reactions caused by the retention of reaction products inside the catalysts are reduced, and the reaction activity and propylene selectivity are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a SEM image of the cross section of the shaped molecular sieve catalyst prepared in Example 1 of the present invention.

[0050] Figure 2 This is a SEM image of the interior of the shaped molecular sieve catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.

[0052] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0053] The present invention will be described in detail below through examples.

[0054] Example 1

[0055] 100g of NH4-ZSM-5 molecular sieve with a silicon-aluminum ratio of 500, 6g of acrylic fiber porogen-1 with an aspect ratio of 200, 6g of microcrystalline cellulose porogen-2 with an aspect ratio of 1, and 4g of sesbania powder were added to a 300ml kneader and mixed evenly. Then 50g of 40% silica sol was added and kneaded for 30 minutes, during which an appropriate amount of distilled water was added, and the kneaded material became a plastic material with appropriate dryness and wetness.

[0056] By extrusion and pelletization, a catalyst body with a diameter of 2.5 mm and a length of 5 mm was prepared.

[0057] Then, the catalyst was aged in air at 20°C for 24 hours and then dried in an oven at 120°C for 24 hours. Finally, the dried green body was heated to 600°C in a muffle furnace at a heating rate of 30°C / hour and calcined for 2 hours to obtain a catalyst with a porous structure.

[0058] Take 25g of the above catalyst and load it into a stainless steel reactor with an inner diameter of 25. Take mixed C4 with a mass fraction of 70% butene-1 as raw material and heat it at normal pressure, 530℃ and a raw material weight space velocity of 20h -1 The test of butene cracking to produce propylene was carried out under the following conditions, and the results are shown in Table 1.

[0059] Example 2

[0060] 100g of NH4-ZSM-5 molecular sieve with a silicon-aluminum ratio of 500, 12g of acrylic porogen-1 with an aspect ratio of 500, 2.4g of nylon porogen-2 with an aspect ratio of 10, and 4g of sesbania powder were added to a 300ml kneader and mixed evenly. Then 50g of 40% silica sol was added and kneaded for 30 minutes, during which an appropriate amount of distilled water was added, and the kneaded material became a plastic material with appropriate dryness and wetness.

[0061] By extrusion and pelletization, a catalyst body with a diameter of 2.5 mm and a length of 5 mm was prepared.

[0062] Then, the catalyst was aged in air at 25°C for 48 hours and then dried in an oven at 120°C for 24 hours. Finally, the dried green body was heated to 520°C in a muffle furnace at a heating rate of 50°C / hour for 6 hours to obtain a catalyst with a porous structure.

[0063] 25 g of the above catalyst was taken and loaded into a stainless steel reactor with an inner diameter of Φ25. The catalyst reaction performance was evaluated under the same conditions as in Example 1. The results are shown in Table 1.

[0064] Example 3

[0065] 100g of NH4-ZSM-5 molecular sieve with a silicon-aluminum ratio of 500, 2.4g of acrylic porogen-1 with an aspect ratio of 300, 12g of nylon porogen-2 with an aspect ratio of 10 and 4g of sesbania powder were added to a 300ml kneader and mixed evenly. Then 50g of 40% silica sol was added and kneaded for 30 minutes, during which an appropriate amount of distilled water was added, and the kneaded material became a plastic material with appropriate dryness and wetness.

[0066] The catalyst body with a diameter of 2.5 mm and a length of 5 mm was prepared by extrusion and pelletization. Then, it was aged in air at 25°C for 48 hours and then dried in an oven at 120°C for 24 hours. Finally, the dried body was heated to 550°C in a muffle furnace at a heating rate of 40°C / hour for 6 hours to obtain a catalyst with a porous structure.

[0067] 25 g of the above catalyst was taken and loaded into a stainless steel reactor with an inner diameter of Φ25. The catalyst reaction performance was evaluated under the same conditions as in Example 1. The results are shown in Table 1.

[0068] Example 4

[0069] 100g of NH4-ZSM-5 molecular sieve with a silicon-aluminum ratio of 500, 6g of acrylic porogen-1 with an aspect ratio of 100, 6g of nylon porogen-2 with an aspect ratio of 20, and 4g of sesbania powder were added to a 300ml kneader and mixed evenly. Then 50g of 40% silica sol was added and kneaded for 30 minutes, during which an appropriate amount of distilled water was added, and the kneaded material became a plastic material with appropriate dryness and wetness.

[0070] By extrusion and pelletization, a catalyst body with a diameter of 2.5 mm and a length of 5 mm was prepared.

[0071] Then, the catalyst was aged in air at 25°C for 48 hours and then dried in an oven at 120°C for 24 hours. Finally, the dried body was heated to 520°C in a muffle furnace at a heating rate of 50°C / hour for 6 hours to obtain a catalyst with a porous structure.

[0072] 25 g of the above catalyst was taken and loaded into a stainless steel reactor with an inner diameter of Φ25. The catalyst reaction performance was evaluated under the same conditions as in Example 1. The results are shown in Table 1.

[0073] Example 5 to Example 10

[0074] The catalyst preparation steps were the same as those in Example 4, except that porogen-1 with different aspect ratios was used to prepare the catalyst. The catalyst reaction performance was evaluated under the same conditions as in Example 1. The results are shown in Table 1.

[0075] Example 11 to Example 16

[0076] The catalyst preparation steps were the same as those in Example 4, except that porogen-2 with different aspect ratios was used to prepare the catalyst. The catalyst reaction performance was evaluated under the same conditions as in Example 1. The results are shown in Table 1.

[0077] Embodiment 17

[0078] The catalyst preparation steps are the same as those in Example 2, except that porogen-1 and porogen-2 with different aspect ratios are used and the amount of porogen is changed. The catalyst is prepared by molding and the catalyst reaction performance is evaluated under the same conditions as in Example 2. The results are shown in Table 1.

[0079] Example 18 to Example 20

[0080] According to the same catalyst preparation method as in Example 2, only 6.0 g of each of nylon, polyester and nylon fibers with an aspect ratio of 200 was added to the porogen-1, 6.0 g of nylon with an aspect ratio of 10 and 4 g of sesbania powder were added to a 300 ml kneader and mixed evenly. Then 50 g of 40% silica sol was added and kneaded for 30 minutes, during which an appropriate amount of distilled water was added, and the kneaded material became a plastic material with appropriate dryness and wetness.

[0081] The catalyst body with a diameter of 2.5 mm and a length of 5 mm was prepared by extrusion and pelletization. Then, it was aged in air at 25°C for 48 hours and then dried in an oven at 120°C for 24 hours. Finally, the dried body was heated to 550°C in a muffle furnace at a heating rate of 40°C / hour for 6 hours to obtain a catalyst with a porous structure.

[0082] 25 g of the above catalyst was taken and loaded into a stainless steel reactor with an inner diameter of Φ25. The catalyst reaction performance was evaluated under the same conditions as in Example 1. The results are shown in Table 1.

[0083] Embodiment 21

[0084] 100g of NH4-ZSM-5 molecular sieve with a silicon-aluminum ratio of 500, 6g of acrylic fiber porogen-1 with an aspect ratio of 200, 6g of activated carbon powder porogen-2 with an aspect ratio of 1 and 4g of sesbania powder were added to a 300ml kneader and mixed evenly. Then 50g of 40% silica sol was added and kneaded for 30 minutes, during which an appropriate amount of distilled water was added, and the kneaded material became a plastic material with appropriate dryness and wetness.

[0085] By extrusion and pelletization, a catalyst body with a diameter of 2.5 mm and a length of 5 mm was prepared.

[0086] Then, the catalyst was aged in air at 25°C for 48 hours and then dried in an oven at 120°C for 24 hours. Finally, the dried green body was heated to 550°C in a muffle furnace at a heating rate of 40°C / hour for 6 hours to obtain a catalyst with a porous structure.

[0087] 25 g of the above catalyst was taken and loaded into a stainless steel reactor with an inner diameter of Φ25. The catalyst reaction performance was evaluated under the same conditions as in Example 1. The results are shown in Table 1.

[0088] Embodiment 22

[0089] 100g of NH4-ZSM-5 molecular sieve with a silicon-aluminum ratio of 500, 6g of acrylic porogen-1 with an aspect ratio of 200, 6g of starch porogen-2 with an aspect ratio of 1, and 4g of sesbania powder were added to a 300ml kneader and mixed evenly. Then 50g of 40% silica sol was added and kneaded for 30 minutes, during which an appropriate amount of distilled water was added, and the kneaded material became a plastic material with appropriate dryness and wetness.

[0090] By extrusion and pelletization, a catalyst body with a diameter of 2.5 mm and a length of 5 mm was prepared.

[0091] Then, the catalyst was aged in air at 25°C for 48 hours and then dried in an oven at 120°C for 24 hours. Finally, the dried green body was heated to 550°C in a muffle furnace at a heating rate of 40°C / hour for 6 hours to obtain a catalyst with a porous structure.

[0092] 25 g of the above catalyst was taken and loaded into a stainless steel reactor with an inner diameter of Φ25. The catalyst reaction performance was evaluated under the same conditions as in Example 1. The results are shown in Table 1.

[0093] Comparative Example 1

[0094] The catalyst was prepared according to the method of Example 1, but without adding porogens 1 and 2.

[0095] Add 100 g of NH4-ZSM-5 molecular sieve with a silicon-aluminum ratio of 500 and 4 g of sesbania powder into a 300 ml kneader and mix evenly, then add 50 g of 40% silica sol and knead for 30 minutes, during which time add appropriate amount of distilled water to knead the material into a plastic material with appropriate dryness and wetness.

[0096] By extrusion and pelletization, a catalyst body with a diameter of 2.5 mm and a length of 5 mm was prepared.

[0097] Then, the catalyst was aged in air at 20°C for 24 hours, and then dried in an oven at 120°C for 24 hours. Finally, the dried green body was heated to 600°C in a muffle furnace at a heating rate of 30°C / hour and calcined for 2 hours to obtain a catalyst. The catalyst reaction performance was evaluated under the same conditions as in Example 1, and the results are shown in Table 1.

[0098] Comparative Example 2

[0099] The catalyst was prepared according to the method of Example 1 without adding porogen-2.

[0100] 100g of NH4-ZSM-5 molecular sieve with a silicon-aluminum ratio of 500, 12g of acrylic porogen-1 with an aspect ratio of 200, and 4g of sesbania powder were added to a 300ml kneader and mixed evenly. Then 50g of 40% silica sol was added and kneaded for 30 minutes, during which an appropriate amount of distilled water was added. The kneaded material became a plastic material with appropriate dryness and wetness, and was prepared into a catalyst body with a diameter of 2.5mm and a length of 5mm by extrusion and pelletization.

[0101] Then, the catalyst was aged in air at 20°C for 24 hours and then dried in an oven at 120°C for 24 hours. Finally, the dried green body was heated to 600°C in a muffle furnace at a heating rate of 30°C / hour and calcined for 2 hours to obtain a catalyst with a porous structure. The catalyst reaction performance was evaluated under the same conditions as in Example 1, and the results are shown in Table 1.

[0102] Comparative Example 3

[0103] The catalyst was prepared according to the method of Example 1 without adding porogen-1.

[0104] 100g of NH4-ZSM-5 molecular sieve with a silicon-aluminum ratio of 500, 12g of microcrystalline cellulose with an aspect ratio of 1, and 4g of sesbania powder were added to a 300ml kneader and mixed evenly. Then 50g of 40% silica sol was added and kneaded for 30 minutes, during which time an appropriate amount of distilled water was added to knead the material to become a plastic material with appropriate dryness and wetness.

[0105] By extrusion and pelletization, a catalyst body with a diameter of 2.5 mm and a length of 5 mm was prepared.

[0106] Then, the catalyst was aged in air at 20°C for 24 hours and then dried in an oven at 120°C for 24 hours. Finally, the dried green body was heated to 600°C in a muffle furnace at a heating rate of 30°C / hour and calcined for 2 hours to obtain a catalyst with a porous structure. The catalyst reaction performance was evaluated under the same conditions as in Example 1, and the results are shown in Table 1.

[0107] Table 1

[0108]

[0109] In the above table, the mass content of porogen-1 = [mass of porogen-1 / (mass of NH4-ZSM-5 molecular sieve + mass of silica sol × 40%)] × 100%;

[0110] The mass content of porogen-2=[mass of porogen-2 / (mass of NH4-ZSM-5 molecular sieve+mass of silica sol×40%)]×100%.

[0111] From the data in Table 1, it can be seen that the pores of the catalyst prepared by using two porogens with different aspect ratios have certain openings, which has a certain effect on improving the diffusion within the catalyst. In the olefin cracking reaction, it has a certain effect on improving the reaction activity and selectivity.

[0112] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a shaped molecular sieve catalyst, comprising the following steps: S1: providing a first mixture including molecular sieve raw powder, a first porogen and a second porogen; S2: subjecting the first mixture in S1 to a molding process to obtain a molded product; S3: calcining the formed product in S2 to obtain the formed molecular sieve catalyst; The aspect ratio of the first porogen is greater than that of the second porogen, the aspect ratio of the first porogen is 50-10000, and the aspect ratio of the second porogen is 0.5-50.

2. The preparation method according to claim 1, characterized in that: The aspect ratio of the first porogen is 100-2000, preferably 100-1000; and / or The aspect ratio of the second porogen is 1-30.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the second porogen to the first porogen is (0.05-20):1, preferably (0.1-10):

1.

4. The preparation method according to any one of claims 1 to 3, characterized in that The first porogen is selected from one or more of synthetic fibers and natural fibers. Preferably, the synthetic fibers are selected from one or more of nylon fibers, polyester fibers, nylon fibers, acrylic fibers, polyethylene fibers, polypropylene fibers and polystyrene fibers, and the natural fibers are selected from one or more of broadleaf pulp fibers, coniferous pulp fibers and straw fibers.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The second porogen is selected from one or more of synthetic fibers, synthetic microspheres, microcrystalline cellulose, short fibers, activated carbon, starch and graphite. Preferably, the synthetic fibers are selected from one or more of nylon fibers, polyester fibers, nylon fibers, acrylic fibers, polyethylene fibers, polypropylene fibers and polystyrene fibers.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The first mixture also includes a binder, an extrusion aid and water, Preferably, based on the total mass of the molecular sieve raw powder and the dry-based binder, the mass content of the first porogen is 0.5%-20%, preferably 1%-10%; the mass content of the second porogen is 0.5%-20%, preferably 1%-10%; the mass content of the binder is 5%-50%, preferably 10%-30%; the mass content of the extrusion aid is 0.5%-15%, preferably 1%-8%; Preferably, the extrusion aid is selected from one or more of sesbania powder, modified cellulose, glycerol and polycarboxylic acid; Preferably, the binder is selected from one or more of silica sol, alumina sol, pseudo-boehmite and water glass.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The molecular sieve is selected from one or more of Y-type molecular sieve, ZSM-5 molecular sieve, ZSM-11 molecular sieve, ZSM-35 molecular sieve and mordenite molecular sieve, preferably ZSM-5 molecular sieve.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In S3, before calcination, the molded product is subjected to aging treatment and drying treatment in sequence; Preferably, the temperature of the aging treatment is less than or equal to 80°C, preferably less than or equal to 50°C, and the time of the aging treatment is 2h-48h, preferably 5h-24h; Preferably, the temperature of the drying treatment is 100°C-200°C, preferably 120°C-150°C; the time of the drying treatment is 5h-24h, preferably 5h-15h.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The calcination temperature is 200°C-700°C, preferably 450°C-650°C; the calcination time is 1h-10h, preferably 2h-8h; preferably, the calcination temperature is achieved by programmed temperature increase, and the temperature increase rate is 20°C / h-50°C / h.

10. Use of a shaped molecular sieve prepared by the preparation method according to any one of claims 1 to 9 in a carbon four cracking reaction to produce olefins.

Citation Information

Patent Citations

  • Method for preparing styrene catalyst through ethylbenzene dehydrogenation

    CN101623641A

  • Method for producing ethylene and propylene

    US6307117B1

  • Preparation method for Al2O3 ceramic material having controllable bimodal porous structure

    CN102746022A

  • Extrusion molding method of TS-1 titanium silicalite molecular sieve catalyst

    CN103041852A

  • Protective agent of coal tar hydrogenation catalyst and preparation method of protective agent

    CN103706408A